MODERN ARABIC POETRY CRITICSM FORM AHMAD AMIN’S PERSPECTIVE - Ni'ma Royyin Husnaya; Titin Ardiyanti; Saddam Reza Hamidi; Nida Adzkiya (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
The development of modern Arabic literature has brought about significant changes in the field of Arabic poetry, mainly due to the influence of Western literary traditions that encouraged poets to move away from classical Arabic conventions. Many modern Arab poets began to abandon the rules of 'arūḍ and traditional poetic structures, resulting in a shift away from the classical characteristics of Arabic poetry. This situation sparked a debate among Arab intellectuals regarding the essence and identity of Arabic poetry in the modern era. Against this background, Ahmad Amīn, through his book An-Naqd al-Adabī, offered a critical reflection on poetry and emphasized the importance of preserving the heritage of Arabic literary tradition. This research aims to describe the concept of poetry criticism in Ahmad Amīn's view in An-Naqd al-Adabī. This research uses a type of library research with a descriptive qualitative approach. The results showed that as a historian, Ahmad Amin emphasized the historical-cultural approach in literature, where literature is seen not as something that stands alone, but rather the result of the historical, social, and cultural context of a society. Nonetheless, he retains the values of classical literature, where he believes literature should retain its moral function; by building morals and providing role models.